Accurate diagnoses, evidence based drugs, and new devices (3 Ds) in heart failure (Medical Journal of Indonesia, 2012)
Heart failure becomes main problem in cardiology because of increasing of heart failure patients, rehospitalization rate, morbidity, and mortality rate. The main causes of increasing heart failure problems are: (1) Successful treatment of acute myocardial infarction can be life saving, but its sequelae can cause heart failure. (2) Increasing life expectancy rate grows along with incidences of ageing related heart failure. (3) High prevalence of infection in Indonesia can cause rheumatic heart disease post Streptococcal beta hemolyticus infection, viral myocarditis, infective endocartitis, and tuberculoid pericarditis. (4) Many risk factors for coronary heart disease are often found in heart failure patients, for examples smoking, diabetes, hypercholesterolemia, hypertension, and obesity. Indonesia joined international multicentered registry in 2006. Acute Decompensated HEart failure REgistry is a web based international registry to record patient with acute decompensated heart failure treated in emergency room. It was found that heart failure patients in 5 big hospitals in Java and Bali island that joined this registry are younger, sicker and late to seek treatment. The median hospital length of stay was 7 days and in hospital mortality rate was 6.7%. The aim of this article is to give summary about essential things in diagnosing and treating heart failure patients. 3D (accurate diagnoses, evidence based drugs, and new devices) are the most important but what to do and what not to do in dealing with heart failure is also useful for your daily practice. (Med J Indones 2012;21:52-8)Keywords: Devices, diagnostic, drugs, heart failure